Studi Karakteristik dan Spirit of Place Bangunan Dia.Lo.Gue Artspace - Michelle Aprilia Wijaya; Danang H. Wibowo (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2020)
Each place has a Spirit of Place (soul of a place) or their respective identities - each different. A place that has no soul or Spirit of Place does not have a meaning that can be felt by its visitors. The meaning or impression caused by a place affects the attachment between the individual's soul and the individual's place. This study describes academically the characteristics and Spirit of Place in the Dia.Lo.Gue Artspace building, located at Jalan Kemang, South Jakarta. The Artspace and office are the buildings of famous Indonesian architects, Andra Matin. This study uses descriptive qualitative research methods with case study research methods. This research is expected to produce conclusions about the study of Spirit of Place in a building, and can be used to add insight and add architectural studies about Spirit of Place for those who have an interest related to the case study.